Detection And Analysis Of Malware (Trinity Journal of Management, IT & Media (TJMITM), 2014)
The paper will begin with an introduction describing the various types of  malware. Types of malware described include Virus, Worms, Trojans,  Adware, Spyware, Backdoors and Rootkits that can disastrously affect a  Microsoft Windows operating system.  A brief description of the steps of an incident response plan will be  described. The role of malware analysis and what steps it pertains to in  an incident response plan will be described. The next section will discuss  the goals to be accomplished by performing malware Analysis. After  discussing malware acquisition for malware analysis, a methodology is  presented for performing malware analysis.
Keywords: Worm; Malware; Trojan horses